ADMINISTERING IMMIGRANT INTEGRATION - Ma, Jiajia (My University, 2008)
Most research in immigration studies has so far mainly focused on immigration politics. Other comparative policy studies have drawn upon a huge amount of statistical materials and descriptive documents on social structural, socioeconomic and demographic consequences and trends of those migration flows. In relatively fewer cases, research focused on to a comparative study of administration of immigrant integration. This study concentrates on immigrant integration issue within a theoretical framework of public administration. It aims at exploring the meaning of public administration of immigrant integration, particularly the fundamental administrative processes in immigrant integration and how these processes relate to each other. The goal of administering immigrant integration is to successfully integrate immigrants into the host society by making and implementing integration policies. Immigrant integration also belongs to the social policy domain as there are a lot of policy analyses involved in the study of administrative processes. Drawing on the crucial relation between comparative public policy and administration, the thesis analyses the significance of applying a comparative approach to the study of administrative processes of integration. Furthermore, this study includes a comparative empirical observation of different administrative processes of integration in Germany, Sweden and Finland. The empirical work is conducted on the basis of studying numerous documentary materials selected from the published work done by international organisations or immigration and integration studying groups during the recent decade. By combining the theoretical and empirical analysis together, this thesis finds that administering immigrant integration is based upon the legal, managerial and socio-cultural administrative processes. The three are closely linked to each other. Each process involves a particular policy process of integration and is aimed at solving specific aspect of the general problems in the administration of immigrant integration. Different immigrant receiving countries share the same process structure in general yet show differences in specific policies and institutional structures involved in each of those processes. In addition, an effective administration of integration in the future requires the active participation of various actors in the integration process. Therefore, a mechanism of good communication and cooperation should be widely established. Also, government needs to look for a new role in contemporary immigrant integration, when comparative studies on different organisational structures will contribute to the development of a more flexible and adaptive structure base in responding to the increasing complexity in immigrant integration process.
Keywords: Immigrant integration; public administration; comparative public policy; administrative processes; comparative public administration.; fi=Public Administration|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|